ENHANCING PROTEIN UTILIZATION AND GROWTH PERFORMANCE IN STRIPED CATFISH WITH CINNAMALDEHYDE AND OPTIMIZED ENERGY-TO-PROTEIN RATIOS - Wahyudi, Imam Tri; Jusadi, Dedi; Setiawati, Mia; Ekasari, Julie; Suprayudi, Muhammad Agus; Kurniawinata, Mohamad Iqbal; Imlani, Ainulyakin Hasan (Agency for Marine and Fisheries Extension and Human Resources, 2025)
Efficient dietary protein utilization is essential to reduce feed costs and environmental impacts in sustainable aquaculture. This study aimed to evaluate the effects of cinnamaldehyde (CA) supplementation in feed with various energy-to-protein (E:P) ratios on the chemical composition of Pangasianodon hypophthalmus. The five feed formulas that made up the treatment feed were as follows: 28:13-C0 (28 % Protein with an E:P ratio of 13 and CIN 0 g kg-1); 25:14-C1 (25 % protein with an E:P ratio of 14 and CIN 1.2 g kg-1); 25:14-C2 (25 % protein with an E:P ratio of 14 and CIN 1.7 g kg-1); 25:15-C1 (25 % protein with an E:P ratio of 15 and CIN 1.2 g kg-1); and 25:15-C2 (25 % Protein with an E:P ratio of 15 and CIN 1.7 g kg-1). Striped catfish weighing 28.06 ± 0.19 g were placed in a hapa (2 × 1 × 1 m3) at a density of 25 fish per cage. Fish were fed to apparent satiation three times daily for 60 d. The 25:14-C2, 25:15-C1, and 25:15-C2 diets increased albumin levels and reduced cholesterol, while 25:15-C2 also yielded the highest total protein and lowest triglyceride levels. Growth performance and feed efficiency were comparable among 28:13-C0, 25:14-C2, 25:15-C1, and 25:15-C2 (final weight: 141.62–143.75 g; FCR: 1.16–1.19). Protein efficiency ratio was highest in 25:15-C1 and 25:15-C2, whereas protein retention peaked in 25:14-C2. The hepatosomatic index was elevated in 25:14-C1, 25:14-C2, and 25:15-C1. Body lipid content was highest in 25:15-C1, while muscle lipid content was lowest in 25:14-C2 and 25:15-C1. Reducing dietary protein from 28 % to 25 % did not compromise growth performance at the E:P ratio level of 15 with a supplementation of 1.2 g kg-1 CIN.